Pengaruh Unggahan Akun Instagram @Naqitakarnn Pada Outfit Of The Day Mahasiswi Universitas Islam Negeri Sumatera Utara - Sulastri, Rukma; Deni, Indira Fatra; Rozi, Fakhrur (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research aims to find out how much influence uploads from the Instagram account @naqitakarnn have on the outfit of the day of North Sumatra State Islamic University students. In this research, researchers used descriptive quantitative research methods with simple linear regression research techniques. The population in this study was 300 respondents and the sample was 45 respondents. The theory used in this research is S O R (Stimulus Organism Response) Theory. The data collection method in this research uses questionnaires. Data analysis used descriptive statistical analysis and simple linear regression analysis. Data processing was carried out with the help of SPSS software version 23. Based on the results of the hypothesis testing research, the t test results were Instagram account upload variable @naqitakarnn greater than table or 6.199 > 2.016 with a significance level below 0.05, namely 0.00 0. Thus, it can be concluded that H0 is rejected and Ha is accepted, meaning that there is a positive and moderate influence between the Instagram account upload variable @naqitakarnn on students' outfit of the day. Based on the results of the coefficient of determination (R2), the value (R2) is 0.472 = 47%. This shows that the percentage contribution of uploads from the Instagram account @naqitakarnn to the consumer behavior of Communication Science Students at the State Islamic University of North Sumatra is 47%.